PENINGKATAN KETERAMPILAN SISWA BERMAIN PIANIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN EXPLICIT INTRUCTIONDI KELAS V SD - Suriati, Titit (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This class action research play at pianika by using the explicit intruction. The subject of this research is teacher and student of grade five elementary school 27 Dusun Tuo Kecamatan Lima Kaum Kabupaten Tanah Datar. Intruction explicit learning model is an approach to learning that can help teach students the basic skills to obtain information. The study, carried out an action research using qualitative and quantitative approaches. The design of this study include: action planning, action, observation, and reflection. The results showed an increase in the student learning outcomes in learning SBK, using explicit learning model intruction. Kata kunci : Keterampilan, Bermain, Pianika;  Model Explicit Intruction